2022
DOI: 10.1186/s12955-022-02014-9
|View full text |Cite
|
Sign up to set email alerts
|

Food-related quality of life in inflammatory bowel disease: measuring the validity and reliability of the Turkish version of FR-QOL-29

Abstract: Purpose Food-related quality of life is considerably impaired in patients with inflammatory bowel disease (IBD) and should be widely measured in research and clinical practice. This study aims to translate the FR-QoL-29 instrument to the Turkish language and evaluate its validity and reliability in Turkish patients with IBD. Methods The FR-QoL-29 was forwards and backwards translated into Turkish and the validity and reliability of the FR-QoL-29-Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The largest study to date in 1221 outpatients with IBD in the United Kingdom [ 13 ], reported a high prevalence of impaired FR-QoL in IBD, with lower scores associated with the number of recent disease flares, reduced IBD-specific quality of life and greater IBD-related distress, with impaired FR-QoL being associated with lower intakes of fibre and several micronutrients. Similar low FR-QoL scores have been observed in people with IBD in both the United States [ 14 ], Australia [ 15 ], New Zealand [ 16 ], and Turkey [ 17 ]. A study in active and inactive IBD [ 3 ] showed that the strongest predictor of FR-QoL was IBD symptom severity.…”
Section: Introductionsupporting
confidence: 68%
“…The largest study to date in 1221 outpatients with IBD in the United Kingdom [ 13 ], reported a high prevalence of impaired FR-QoL in IBD, with lower scores associated with the number of recent disease flares, reduced IBD-specific quality of life and greater IBD-related distress, with impaired FR-QoL being associated with lower intakes of fibre and several micronutrients. Similar low FR-QoL scores have been observed in people with IBD in both the United States [ 14 ], Australia [ 15 ], New Zealand [ 16 ], and Turkey [ 17 ]. A study in active and inactive IBD [ 3 ] showed that the strongest predictor of FR-QoL was IBD symptom severity.…”
Section: Introductionsupporting
confidence: 68%